“Green” synthesis of nanoparticles of precious metals: antimicrobial and catalytic properties - Skiba, Margarita; Vorobyova, Viktoria; Pivovarov, Alexander; Shakun, Anastasiia; Gnatko, Elena; Trus, Inna (Eastern-European Journal of Enterprise Technologies, 2018)
The paper presents the use of agricultural products, namely grape skins, in the “green” synthesis of monometallic (Au, Ag) and bimetallic (Au-Ag) nanoparticles (NPs) from aqueous solutions of metal ions of the corresponding precursors. At present, there exist urgent problems of utilization of waste from the agro-industrial complex, rational use of nature and transition to the use of environment-friendly and energy-efficient technologies. Therefore, there is a tendency to use “green” technologies in obtaining nanomaterials that are considered environment-friendly and resource-saving. The study has proved the efficiency of using food waste (grape skins) as a reducing and stabilizing agent in forming nanoparticles of precious metals of mono- and bimetallic structures. Biological raw materials were extracted in an aqueous medium under a short-term effect of low-temperature plasma discharges. On the basis of the complex analysis of the extract composition, it was proved that the hydroxyl, carbonyl and carboxyl functional groups of the organic compounds of the grape skin extract are responsible for the recovery of the metal ions and stabilization of the resulting NPs. The research has proved that mono- and bimetallic NPs are formed with the following peaks: for Ag0 (λmax=440 nm), Au0 (λmax=540 nm), and Ag-Au (λmax=510 nm). The size and stability of the nanoparticles obtained by the “green” synthesis were assessed in comparison with the same parameters for the plasmochemical method of nanoparticles’ formation. The study has revealed antibacterial, catalytic and anti-corrosion properties of the synthesized nanoparticles. The resulting monometallic (Au, Ag) and bimetallic (Au–Ag) nanoparticles show excellent catalytic activity while recovering p-nitrophenol (4-NPh) to p-aminophenol (4-APh) in the presence of NaBH4. The synthesized NPs demonstrate their antibacterial activity against gram-positive and gram-negative bacteria. The findings allow to expand the practical application of metal nanoparticles in various industries and enhance the processing and reuse of non-liquid waste